2013
DOI: 10.4103/0975-5950.127651
|View full text |Cite
|
Sign up to set email alerts
|

Turmeric - A new treatment option for lichen planus: A pilot study

Abstract: Turmeric is dried rhizome of the perennial herbs curcumalonga. It is called Haldi in Hindi, turmeric in English, ukon in Japanese. It has been used in Asian Medicine since the second millennium BC. It's utility is referred to in the ancient Hindu script the Ayurveda. Pathogenesis of the OLP should be taken in consideration for the treatment point of view. The Cell mediated immunity to secondary antigenic change in oral mucous membrane is thought to play a major role in its pathogenesis modified keratocyte surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 3 publications
1
28
0
Order By: Relevance
“…(a) (b) in all participants and improvement in clinical symptoms in nine patients were reported after three months [24].…”
Section: Discussionmentioning
confidence: 99%
“…(a) (b) in all participants and improvement in clinical symptoms in nine patients were reported after three months [24].…”
Section: Discussionmentioning
confidence: 99%
“…The analysed studies show that there are no statistically significant differences between the use of a 5% curcumin oral paste and the use of topical triamcinolone [22]. Singh et al described curcumin as a new safe option for treating OLP, but they found that its effectiveness is lower than that of steroids [55].…”
Section: Curcuminmentioning
confidence: 99%
“…Singh V et al conducted study on patients of clinically and histological diagnosed oral lichen planus. Turmeric ointment was given to apply topically 2 times a day for 3 months, significant improvement was observed in clinical symptoms [5].…”
Section: Methodsmentioning
confidence: 99%